Quality attributes of Malaysian coconut water (MATAG and MAWA) - Halim, H. H.; Williams-Dee, E.; Pak Dek, Mohd Sabri; Hamid, A.; Ahmad, N.; Jaafar, Ahmad Haniff (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2017)
Coconut water (CW) is a popular natural hydration beverage since it possess high electrolytes content and adequate amount of sugar. This study aimed to compare the physicochemical characteristics, electrolytes and sugars in young and mature CW from two Malaysian hybrid coconut varieties (MATAG and MAWA). As for the results, flesh thickness of nuts and pH of CW in both varieties increased significantly (p<0.05) while nut weight, total soluble solids (TSS) decreased significantly (p<0.05) with maturation of the fruits. Majority of electrolytes decreased as maturity increased in both varieties. Meanwhile for sugar analysis, fructose and glucose decreased significantly (p<0.05) while sucrose increased significantly (p<0.05) in both varieties as maturation of the coconuts take placed. As conclusion, mature CW from both varieties possessed higher electrolytes and sucrose as compared to the CW obtained from the young coconut.